The awareness of effective financial planning among the students of Faculty Business Management UiTM Bandaraya Melaka Campus / Mohd Fuad Othman and Nur Izzati Ayu Abas - Othman, Mohd Fuad; Abas, Nur Izzati Ayu (Faculty of Business and Management, 2014)
The awareness of financial planning among university students has become decreasing attention. The purpose of this study is to examine the personal knowledge, personal value, risk and return investment, and subjective to awareness of effective financial planning among university students. Data were collected from 200 respondents in Faculty of Business Management in UiTM Bandaraya Melaka campus. Conceptual framework has been designed for the research which the independent variables; personal knowledge, personal value and risk and return investment which affect the awareness of financial planning. Personal knowledge has the greatest effect on the awareness of financial planning among university students. Overall, the implication and recommendations for the future research also provided for the parents, university or college administrators, counselors and also educators.